dGTP starvation in Escherichia coli provides new insights into the thymineless-death phenomenon. - Mark Itsko; Roel M Schaaper (PLoS Genetics)
Starvation of cells for the DNA building block dTTP is strikingly lethal (thymineless death, TLD), and this effect is observed in all organisms. The phenomenon, discovered some 60 years ago, is widely used to kill cells in anticancer therapies, but many questions regarding the precise underlying mechanisms have remained. Here, we show for the first time that starvation for the DNA precursor dGTP can kill E. coli cells in a manner sharing many features with TLD. dGTP starvation is accomplished by combining up-regulation of a cellular dGTPase with a deficiency of the guanine salvage enzyme guanine-(hypoxanthine)-phosphoribosyltransferase. These cells, when grown in medium without an exogenous purine source like hypoxanthine or adenine, display a specific collapse of the dGTP pool, slow-down of chromosomal replication, the generation of multi-branched nucleoids, induction of the SOS system, and cell death. We conclude that starvation for a single DNA building block is sufficient to bring about cell death.